Production of chili pepper under organic fertilization and irrigation with treated wastewater - Viviane F. Silva; Carlos V. C. Bezerra; Elka C. S. Nascimento; Tricia N. F. Ferreira; Vera L. A. Lima; Leando O. Andrade (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT With the occurrence of prolonged droughts in the Brazilian semi-arid region, water scarcity directly influences agriculture in this region, so that water reuse and bovine manure application become a viable alternative for pepper production. In this context, the present study aimed to evaluate the sustainable production of chili peppers (Capsicum frutescens) under levels of irrigation with treated wastewater and doses of bovine manure. The following bovine manure doses were considered: D1 (0% manure and 100% soil), D2 (10% manure and 90% soil), D3 (20% manure and 80% soil), D4 (30% manure and 70% soil), D5 (40% manure and 60% soil) and D6 (50% manure and 50% soil), based on volume. Three levels of irrigation were applied, based on the water requirement of the crop (WR), namely: 100% WR (L1), 75% WR (L2) and 50% WR (L3). Production variables and physical characteristics of the produced peppers were evaluated. Pepper production (g plant-1) increased as 10% of bovine manure were added in substrate composition. Increasing concentration of bovine manure and using 50% WR provided favorable conditions for the organic production of chili pepper.